2021
DOI: 10.1038/s41598-021-01291-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of insomnia as an environmental risk factor for asthma via Mendelian randomization and gene environment interaction

Abstract: Asthma is a complex disease that is reportedly associated with insomnia. However, the causal directionality of this association is still unclear. We used asthma and insomnia-associated single nucleotide polymorphisms (SNPs) and genome-wide association study (GWAS) summary statistics to test the causal directionality between insomnia and asthma via Mendelian randomization (MR) analysis. We also performed a cross-trait meta-analysis using UK Biobank GWAS summary statistics and a gene–environment interaction stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Unfortunately, we could not find evidence that genetically predicted allergic disease, asthma, or moderate-to-severe asthma was causally linked with the increased risk of insomnia. The similar finding was observed by another MR analysis [12]. It seems that not all epidemiological link can be confirmed by MR study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Unfortunately, we could not find evidence that genetically predicted allergic disease, asthma, or moderate-to-severe asthma was causally linked with the increased risk of insomnia. The similar finding was observed by another MR analysis [12]. It seems that not all epidemiological link can be confirmed by MR study.…”
Section: Discussionsupporting
confidence: 84%
“…Insomnia is highly prevalent among patients with allergic disease, and it is reported that 44% to 70% of asthma patients and 33% to 87% of atopic dermatitis people have symptoms of insomnia [8,9]. And the converse is also true that poor sleep itself could cause or worsen allergic disease [8][9][10][11][12]. Two longitudinal observational studies have provided supportive evidence that insomnia carried an increased risk of newly-onset asthma [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Polygenic risk score (PRS) approaches show an increased potential to detect significant GxE in complex traits compared with methods based on individual SNPs 54,55 . Mendelian Randomization (MR) strategies also promise to provide additional insights into the causality and directionality of GxE, 56 although they have been scarcely applied to evaluate the mechanisms underlying asthma 57 …”
Section: Expanding the Gene‐environment Conceptmentioning
confidence: 99%
“…4 In addition, asthma can also affect sleep duration, sleep quality, napping and daytime sleepiness. [5][6][7][8] However, the association between sleep and asthma may be bidirectional. There could be a possibility that not only can asthma influence sleep quality, but poor sleep itself could also cause or worsen asthma.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…For example, poor sleep quality and obstructive sleep apnoea were reported more commonly in patients with asthma, especially those with severe asthma 4. In addition, asthma can also affect sleep duration, sleep quality, napping and daytime sleepiness 5–8. However, the association between sleep and asthma may be bidirectional.…”
Section: Introductionmentioning
confidence: 99%